2021
DOI: 10.1371/journal.pone.0258445
|View full text |Cite
|
Sign up to set email alerts
|

Porcine placenta hydrolysate as an alternate functional food ingredient: In vitro antioxidant and antibacterial assessments

Abstract: The production of bioactive peptides from animal-based raw materials highly depends on enzymatic hydrolysis. Porcine placenta is an underutilized biomass in Thailand’s pig farms, yet it is still a source of proteins and beneficial compounds. Porcine placenta could be used as a protein substrate for the production of enzymatic hydrolysate, which could be employed as a functional food ingredient in the future. The goal of this study was to enzymatically produce porcine placenta hydrolysates (PPH) using three com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…The peptides obtained from goat placenta have a good scavenging effect on 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radicals in a concentration-dependent manner [ 8 ]. Porcine placenta hydrolysate had an excellent reducing capacity, metal chelating ability and higher DPPH and ABTS inhibitory activities [ 21 ]. The results of this study indicated that the ABTS radical scavenging power of CPE is 19.56 μmol/g, the FRAP reducing the power of CPE is 43.62 μmol/g, and the Ferrozine inhibition rate of 50 mg/mL CPE can reach 72.60%.…”
Section: Discussionmentioning
confidence: 99%
“…The peptides obtained from goat placenta have a good scavenging effect on 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radicals in a concentration-dependent manner [ 8 ]. Porcine placenta hydrolysate had an excellent reducing capacity, metal chelating ability and higher DPPH and ABTS inhibitory activities [ 21 ]. The results of this study indicated that the ABTS radical scavenging power of CPE is 19.56 μmol/g, the FRAP reducing the power of CPE is 43.62 μmol/g, and the Ferrozine inhibition rate of 50 mg/mL CPE can reach 72.60%.…”
Section: Discussionmentioning
confidence: 99%
“…EPPH has both antioxidant and antibacterial properties. However, the properties vary according to the hydrolysis process and used proteases [ 38 ]. The EPPH used in the present study reduced lipid peroxides in the blood and skeletal muscles by activating the antioxidant system and increasing SOD and GSH-Px activity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, enzymatic porcine placental hydrolysate (EPPH) was extracted using an enzyme hydrolysis method to extract placental-derived peptides recently reported as excellent bioactive substances [ 26 , 27 ], and EPPH was administered to HepG2 cell- and alcohol-derived animal models. As a result, it was confirmed that inflammation and antioxidant activity could be controlled through CYP 2E1 inhibition.…”
Section: Introductionmentioning
confidence: 99%